Coping Using Sex During the Coronavirus Disease 2019 (COVID-19) Outbreak in the United Kingdom. Issue 1 (26th November 2020) - Gillespie, Steven M.; Jones, Andrew; Uzieblo, Kasia; Garofalo, Carlo; Robinson, Eric
ABSTRACT: Background: The use of sex to cope with negative affective states during the coronavirus disease 2019 (COVID-19) pandemic may be influenced by various sociodemographic and psychological characteristics. Aim: We aimed to examine the effects of social distancing, loneliness, difficulties in emotion regulation, and self-regulation on participants self-reported coping using sex during lockdown in the United Kingdom. Methods: Participants had to be residents of the United Kingdom, aged between 18–60 years, fluent in English, and had to have an Internet connection. They were instructed not to participate if they had consumed alcohol in the previous 24 hours. A total of 789 participants aged 18–59 years completed an online survey. Participants provided self-report measures of social distancing, loneliness, and difficulties in emotion regulation. A Go/No-Go task was used to assess self-regulation. Outcomes: Participants self-reported their use of sex to cope over a 14-day period during lockdown, as well as retrospectively for a 14-day period immediately preceding lockdown. Coping using sex items included consensual and non-consensual themes. RESULTS: Overall, there was no increase in coping using sex during lockdown compared with before lockdown. Findings showed that 30% of participants reported increased coping using sex during lockdown compared with before, 29% reported decreased coping using sex, and 41% reported no change. All regression models included age, gender, ethnicity, diagnosis of psychiatric condition, level of education, being at high-risk for difficulties relating to COVID-19, living alone, and diagnosed or suspected COVID-19 as covariates. Being younger, being male, and greater emotion dysregulation were associated with higher coping using sex total and consent subscale scores during lockdown. Being younger, being male, not living alone, and less adherence to social distancing advice were associated with coping using sex with a theme of rape/violence during lockdown. Clinical Translation: A proportion of participants used sex to cope more often during lockdown compared with before. Less adherence to social distancing advice and emotion dysregulation were associated with using sex to cope during lockdown. Strengths & Limitations: Strengths of this study were the large sample size and inclusion of key sociodemographic characteristics as covariates. The main limitations were the cross-sectional design and a sample that was mostly white, educated, and female. CONCLUSION: Participants who had difficulty regulating emotions were more likely to use sex to cope. It is important that support is available for people who have problems regulating their emotions during the pandemic and that they have access to appropriate help and advice.